2008
DOI: 10.1590/s1516-84842008000600010
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do efeito da hipotermia por crioimersão corporal, nos neutrófilos e linfócitos sanguíneos de ratos submetidos ao exercício físico agudo

Abstract: O estresse sistêmico induzido pelo exercício libera substâncias bioativas determinantes da mobilização neutrofílica. A crioterapia diminui a reação inflamatória e atenua a elevação da perfusão sanguínea induzida pelo exercício. O objetivo deste trabalho foi analisar a influência da hipotermia decorrente da crioimersão corporal (CIC) imediata ao esforço físico agudo nas concentrações neutrofílicas e linfocíticas no sangue. Os ratos do grupo controle (AI) foram mantidos em repouso enquanto os do grupo AII foram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
1
0
1
Order By: Relevance
“…In this respect, Nehlsen-Cannarella et al 10 showed that highintensity exercise is associated with a biphasic change in circulating leukocytes. In line with the results of the present study, Bachur et al 8 found a two-to three-fold increase in leukocyte counts above normal values in mice submitted to physical exercise. The return to baseline levels takes about 24 hours after completion of physical exercise 7 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this respect, Nehlsen-Cannarella et al 10 showed that highintensity exercise is associated with a biphasic change in circulating leukocytes. In line with the results of the present study, Bachur et al 8 found a two-to three-fold increase in leukocyte counts above normal values in mice submitted to physical exercise. The return to baseline levels takes about 24 hours after completion of physical exercise 7 .…”
Section: Discussionsupporting
confidence: 93%
“…In this respect, hematological and biochemical markers have been addressed in the literature. The chronic adaptation of red blood cellrelated measures to exercise has been studied [4][5][6] , and the acute response of white blood cell-related measures as markers of immune function has also been addressed 7,8 . In addition, some metabolites that are released into the bloodstream in response to stress induced by exercise, such as creatinine 9 and proteins 10 , are also evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Após a realização do referido esforço físico agudo, todos os indivíduos foram submetidos ao procedimento de imersão corporal até a região xifoidiana, em um tanque de inox (de 80 cm de altura por 60 cm de largura e 100 cm de comprimento) com água a 10°C durante 10 minutos conforme o Protocolo de CIC 17 . A avaliação morfológica do EOx no plasma sanguí-neo foi realizada de acordo com o teste denominado de Microscopia Ótica para a Análise Celular In Vitro ou Teste HLB, também conhecido sob a denominação de Dry layer oxidative test, ao qual nos referimos como morfologia microscópica do EOx no plasma (MEOP).…”
Section: Metodologiaunclassified